Direct Transition of Outgrowing Bacterial Spores to New Sporangia Without Intermediate Cell Division - Vinter, Vladimir (1965)
Vinter, Vladimir (Syracuse University, Syracuse, N.Y.), and Ralph A. Slepecky. Direct transition of outgrowing bacterial spores to new sporangia without intermediate cell division. J. Bacteriol. 90:803–807. 1965.—A direct transition was observed of the primary cell developed after germination of Bacillus cereus spores into new sporangia without intermediate division stages. Two simple methods were used for replacement of outgrowing spores into diluted medium or saline. Elongated primary cells prevented from division by limitation of nutrients in the suspending medium were able to form new forespores in 8 hr and sporangia in 12 hr. These new sporangia were still marked by attached envelopes of the original spore. Under the same conditions, cells replaced during the first divisions quickly lysed. Spores formed in the elongated primary cell during “microcycle sporogenesis” possessed normal heat resistance and refractility and were later released from sporangia.